IFRS 9 Impairment Provisioning Determinants : Evidence from Public Data of European Banks During 2018Q4 – 2024Q2 - Puuska, Jesse (My University, 2025)
Banks’ ability to absorb loan losses and maintain financial stability depends on timely and adequate loan loss provisioning. In 2018, the IFRS 9 accounting standard introduced a forward-looking expected credit loss (ECL) approach to encourage earlier recognition of credit losses and reduce procyclicality. However, the framework allows considerable discretion, which may give rise to variation in provisioning practices across banks. This study investigates the determinants of banks’ impairment provisions under the IFRS 9 regime, with particular attention to discretionary practices such as income smoothing, capital management, and delayed loss recognition, as well as structural outcomes like procyclicality. The analysis applies an empirical model to a panel of European banks covering the period from 2018:Q4 to 2024:Q2. The study is based on publicly available data from the European Banking Authority’s EU-wide Transparency Exercise, comprising more than 2,200 bank-quarter observations across 127 banks in 27 countries. The sample spans a period of significant macro-financial change, including the post-pandemic shift to a rising interest rate environment. This allows for timely examination of the provisioning behaviour under diverse economic conditions. The model relates loan loss provisions to factors reflecting earnings, capital adequacy, credit risk, and macroeconomic conditions, allowing for the assessment of the key hypothesized behaviours. The empirical findings largely align with patterns reported in earlier studies. Provisioning is still used to smooth earnings, as indicated by a significant positive relationship between pre-impairment income and provisions. Unlike in earlier studies, no evidence is found that banks with weaker capital positions provision less, suggesting an absence of capital management effects. Loss recognition remains delayed, with provisions increasing significantly when loans become non-performing. In addition, provisioning under IFRS 9 remains procyclical, despite its forward looking design. These results posit that discretionary provisioning practices persist under IFRS 9. The findings carry important policy implications. They underscore the continued need for supervisory oversight to ensure that banks' use of discretion in provisioning does not undermine transparency or financial stability. Improved disclosure and greater consistency in provisioning practices could help strengthen market discipline and comparability across institutions. By offering timely and comprehensive evidence, this study updates the literature on IFRS 9 impairment behaviour and provides a basis for evaluating the effectiveness of the ECL framework in diverse macro-financial conditions.

Riittävä ja oikea-aikainen varautuminen luottotappioihin tukee pankkien kykyä kestää luottotappiot ja ylläpitää vakavaraisuutta. IFRS 9 -tilinpäätösstandardi toi vuonna 2018 käyttöön ennakoivan odotettuihin luottotappioihin perustuvan lähestymistavan (ECL), jonka tavoitteena oli luottotappioiden aikaisempi kirjaaminen ja vähenevä myötäsyklisyys. IFRS 9 antaa pankeille kuitenkin runsaasti harkinnanvaraa, mikä voi johtaa eroihin varauskäytännöissä. Tässä tutkimuksessa selvitetään pankkien arvonalentumisvarausten määräytymiseen vaikuttavia tekijöitä. Erityinen huomio kiinnitetään harkinnanvaraisiin käytäntöihin, kuten tuloksen hallintaan, pääoman hallintaan ja odotettujen tappioiden viivästyneeseen kirjaamiseen sekä rakenteellisiin ilmiöihin, kuten myötäsyklisyyteen. Tutkimuksessa sovelletaan empiiristä mallia eurooppalaisten pankkien aineistoon ajalta 2018:Q4–2024:Q2. Aineisto perustuu Euroopan pankkiviranomaisen (EBA) julkisiin Transparency Exercise -tietoihin ja kattaa yli 2 200 havaintoa 127 pankista 27 maassa. Tarkasteltava jakso kattaa merkittäviä muutoksia toimintaympäristössä, kuten pandemian jälkeisen korkojen nousun, mahdollistaen ajantasaisen analyysin erilaisissa makrotaloudellisissa olosuhteissa. Mallissa luottotappiovaraukset yhdistetään pankkien tulokseen, vakavaraisuuteen, luottoriskiin ja talouskehitykseen, mikä mahdollistaa keskeisten käyttäytymisoletusten testaamisen. Empiiriset havainnot ovat pitkälti linjassa aiempien tutkimusten tulosten kanssa. Varauksia käytetään edelleen tuloksen hallintaan, mistä osoituksena on merkittävä positiivinen yhteys arvonalentumiskirjauksia edeltävän tuloksen ja varausmäärien välillä. Aiemmista tutkimuksista poiketen tässä analyysissä ei havaittu todisteita pääoman hallinnasta. Tappioiden kirjaaminen on yhä viivästynyttä ja varaukset kasvavat merkittävästi lainoja luokiteltaessa järjestämättömiksi. IFRS 9:n ennakoivasta luonteesta huolimatta luottotappiovaraukset ovat edelleen myötäsyklisiä. Nämä havainnot viittaavat siihen, että harkinnanvaraiset varauskäytännöt ovat jatkuneet. Tuloksilla on tärkeitä politiikkavaikutuksia. Ne korostavat jatkuvan viranomaisvalvonnan tarvetta sen varmistamiseksi, että pankkien harkinnanvarainen varautuminen ei heikennä läpinäkyvyyttä tai rahoitusvakautta. Tietojen avoimuuden parantaminen ja varauskäytäntöjen yhtenäistäminen voisivat osaltaan vahvistaa markkinakuria ja lisätä vertailukelpoisuutta pankkien välillä. Tarjoamalla ajankohtaista ja kattavaa näyttöä tämä tutkimus päivittää IFRS 9:n mukaista arvonalentumiskäyttäytymistä koskevaa kirjallisuutta ja luo perustan ECL-kehikon tehokkuuden arvioinnille erilaisissa makrotaloudellisissa olosuhteissa.
Keywords: IFRS-standardit; luotot; pankit; luottoriskit; luottotappiot; fi=Taloustiede|en=Economics|; fi=Taloustieteen maisteriohjelma|en=Master's Programme in Economics|